Refractory Chronic Spontaneous Urticaria Treated With Omalizumab in an Adolescent With Common Variable Immunodeficiency - Comberiati, Pasquale; Costagliola, Giorgio; Carli, Niccolò; Legitimo, Annalisa; D'Elios, Sofia; Consolini, Rita; Peroni, Diego G. (Frontiers in Immunology, 2019)
Chronic spontaneous urtcaria (CSU) can represent the leading sign of a wide spectrum of systemic diseases, including primary immunodeficiencies. We describe the case of a young adult female with coexisting CSU and common variable immunodeficiency (CVID) successfully treated with omalizumab. The patient, with a history of recurrent respiratory infections during childhood, was referred to clinical attention due to the development of refractory CSU. During the diagnostic workup for the research of secondary causes of urticaria, an immunological assessment was performed, showing markedly reduced levels of IgG and IgM, poor antibody response against vaccinating antigens in absence of a T cellular deficiency. Therefore, the diagnosis of CVID was posed. Despite the immunoglobulin replacement and a trial with intravenous immunoglobulin at immunomodulatory dosage, the patient continued to experience severe urticaria, with significant impairment in the quality of life. After two years from the diagnosis of CVID, a treatment with omalizumab was started, showing complete remission of cutaneous symptoms after the first injection. The drug was well tolerated, and the patient did not experience adverse effects during a 12-months follow-up.